keria2
keria2
02-11-2015
History
contestada
mult step equation 63=-3(1-2n)
Respuesta :
TSO
TSO
02-11-2015
63 = -3(1-2n)
63 = -3 + 6n
6n - 3 = 63
6n = 66
n = 11
Answer Link
VER TODAS LAS RESPUESTAS ( 87+ )
Otras preguntas
In the step by step simplification of expression below which property is not used? 3(1+x)3(x+1)3(x)+3(1)3x +3 A) associative B) commutative C) distributive D)
Proof: Given: Isosceles trapezoid TRAP with TR=PA Prove: Angle RTA = angle APR
i need with math it say the ride-it store rents bicycles. the cost is $8.50 for 1 hour, $13.64 for 2 hours, $18.80 for 3 hours, and 23.95 for 4 hours. if the pa
i need with math it say the ride-it store rents bicycles. the cost is $8.50 for 1 hour, $13.64 for 2 hours, $18.80 for 3 hours, and 23.95 for 4 hours. if the pa
A laptop computer is priced at $650. If the sales tax is 5%, find the total cost of the computer, including sales tax.
Proof: Given: Isosceles trapezoid TRAP with TR=PA Prove: Angle RTA = angle APR
Proof: Given: Isosceles trapezoid TRAP with TR=PA Prove: Angle RTA = angle APR
In the step by step simplification of expression below which property is not used? 3(1+x)3(x+1)3(x)+3(1)3x +3 A) associative B) commutative C) distributive D)
A laptop computer is priced at $650. If the sales tax is 5%, find the total cost of the computer, including sales tax.
In the step by step simplification of expression below which property is not used? 3(1+x)3(x+1)3(x)+3(1)3x +3 A) associative B) commutative C) distributive D)